Fungal pathogens causing postharvest fruit rot of wolfberry and inhibitory effect of 2,3-butanedione - Ling, Lijun; Luo, Hong; Zhao, Yunhua; Yang, Caiyun; Cheng, Wenting; Pang, Mingmei (Frontiers in Microbiology, 2023)
One of the most critical factors impacting the postharvest quality and shelf life of wolfberry fruits is fungal pathogen infection. As a result, preventing and controlling fungal diseases that cause fruit rot has become critical. Volatile antifungal agents of biological origin have broad application prospects. They may be safer and more efficient than traditional physical and chemical methods. Four pathogenic fungi were isolated and purified from rotting wolfberry, these pathogenic fungi were determined to be Mucor circinelloides LB1, Alternaria iridiaustralis LB5, Alternaria iridiaustralis LB7, Colletotrichum fioriniae LB8. In vitro fumigation tests revealed that 2,3-butanedione can effectively limit pathogenic fungi's mycelial growth, spore germination, and sporulation capabilities. The morphological alterations of hyphae were observed using a scanning electron microscope (SEM). Propidium iodide (PI) staining and 260 and 280 nm-absorbing leakage increased, indicating cell membrane disruption. Furthermore, 2,3-butanedione was found to significantly improve fruit firmness, soluble solid, total phenol, flavonoid, and soluble sugar content, as well as higher SOD enzyme activity and lower PPO and POD enzyme activity in the treated fruit, indicating that 2,3-butanedione can effectively reduce the adverse effects of pathogenic fungi in wolfberry. This study concluded that 2, 3-butaneone can effectively control the pathogenic fungal infection of wolfberry after harvest based on these data. As a result, 2,3-butanedione should be considered as a potential alternative to the existing fungicides used to prevent rot in wolfberry.